Facile grafting method achieves Unprecedented dispersion stability of carbon black in PP fiber - Yaoming Wang; Guihao Liu; Yuqing Liu; Yiqing Zhang; Guangtao Chang; Ruoxin Li (Polymer Testing)
Carbon black (CB) offers valuable properties, but its tendency to agglomerate hinders its full potential in polymer applications. This study presents a novel and straightforward graft modification method to overcome this limitation. By covalently bonding organic functional groups to the CB surface, the surface energy of carbon black was significantly reduced and enhanced its compatibility with organic PP polymers. Characterization techniques (FTIR, XPS, Raman, TGA, etc.) confirm successful grafting and demonstrate excellent dispersion stability of modified CB in organic media. The modified CB exhibits uniform dispersion and reduced particle size within polypropylene (PP) fibers, leading to tensile strength increased dramatically from 103 MPa (unmodified) to 517 MPa (modified). Moreover, the strain reached 1086 %, exceeding both unmodified CB or commercial CB concentrate modified polypropylene (PP) fibers by 31 % and 11 %, respectively. This method represents a significant advancement over existing techniques by providing a straightforward and efficient approach to developing high-strength polypropylene fibers with exceptional tensile and strain characteristics for coloring synthetic fiber applications.